IMPROVING THE METHODOLOGY OF TEACHING STUDENTS SOCIAL AND HUMANITARIAN SCIENCES BASED ON THE COMPETENCE APPROACH (Web of Teachers: Inderscience Research, 2024)
This article thorough mastering of the fundamentals of educational science requires students to fully analyze and synthesize the existing situation, to study all the factors that influence the origin of defects, to take a critical approach to solving the problem, to choose effective methods and methodologies, develops the skills of their purposeful use. At the end of the 19th century and the beginning of the 20th century, a series of researches were carried out in the field of psychology. As a result, the theory of "psychological diagnosis" was founded in the first decades of the 20th century, and the theory of "pedagogical diagnosis" in the last decades. The main idea and research direction of these theories is the analysis and assessment of the quality of education based on the diagnosis of the real situation. He showed the necessity of teaching the educational subject "Pedagogical diagnosis and correction" at the Higher Education Institution. The purpose of the academic discipline "Pedagogical diagnosis and correction" is to create the necessary conditions for the comprehensive development of the student's personality, education, psychologically effective preparation for educational and professional activities based on the identification and use of pedagogically important information. - physical aspect; - the intellectual aspect, which takes into account a certain level of the ability to differentiate (distinguish), as well as the development level of memory; - attitude to work, expressed in the ability to control attention, patience, and complete tasks; - a social aspect that indicates the ability to establish contact with a group to be free from a tutor.